ETIKA PENDIDIKAN DAN TANGGUNG JAWAB MORAL PENDIDIK DI ERA MODERNITAS - Dharmawan, Budi; Fahrurrozi, Fahrurrozi; Imelda, Imelda; Jalinus, Nizwardi; Anwar, Muhammad (Jurnal Manajemen Pendidikan, 2025)
Modernity has brought about profound transformations in the understanding and practice of education. The dominance of instrumental rationality, technological advancement, and an increasing emphasis on efficiency and performance have driven education toward technocratic and pragmatic approaches, potentially diminishing its meaning as a process of holistic human formation. Within this context, the role of educators extends beyond fulfilling professional and administrative demands to confronting increasingly complex ethical tasks related to moral responsibility within pedagogical relationships. This article aims to critically examine the concept of educational ethics and to analyze the moral responsibility of educators in the modern era through the perspective of critical philosophy of education. The study employs a philosophical literature review using normative, hermeneutic, and reflective–critical approaches to both classical and contemporary educational thought. The findings indicate that educational ethics constitutes an ontological and axiological foundation that significantly shapes the direction and quality of pedagogical practice. Educators should not be viewed merely as technical implementers of curricula, but rather as reflective moral subjects responsible for safeguarding the dignity of learners as human beings. This article argues that strengthening educational ethics is an urgent necessity as a critical response to the crises of values, dehumanization, and alienation within modern educational practices, and it contributes to the development of a more humane and meaningful philosophical framework for education.